Research Cluster on Fintech Development in Turkiye - Adam, Muniem (SMART Insight, 2025)
This study aims to analyze the development and research trends of Financial Technology (FinTech) in Türkiye through a bibliometric approach. The data used in this study were obtained from 52 scientific publications indexed in the Scopus database using the keyword “FinTech in Turkiye.” The analysis was conducted using VOSviewer to visualize bibliometric networks, including keyword co-occurrence, author mapping, and thematic clustering. The findings reveal that research on FinTech in Türkiye has grown significantly and can be categorized into four main clusters: (1) FinTech, financial systems, and sustainable economic development; (2) green finance and FinTech; (3) digital transformation and FinTech innovation; and (4) social and economic impacts of FinTech. The results indicate that FinTech plays a crucial role in enhancing financial inclusion, improving the efficiency of financial systems, and supporting sustainable development goals (SDGs). Furthermore, the integration of FinTech with green finance highlights its potential in promoting environmentally sustainable investments, while digital transformation—particularly through artificial intelligence and emerging technologies—acts as a key driver of innovation in the financial sector. Despite its significant contributions, the study also identifies several challenges, including regulatory issues, digital inequality, data security concerns, and institutional readiness. Therefore, a comprehensive and well-regulated approach is necessary to ensure the sustainable growth of the FinTech ecosystem in Türkiye. This study contributes to the existing literature by providing a systematic mapping of FinTech research and offers insights for future research directions, policymakers, and industry practitioners.